Synergistic effects and mechanisms of basalt fibers and polycarboxylate superplasticizer on cement-fly ash stabilized aeolian sand and crushed stones. - Jie Liu; Qinli Liu; Chao Pu; Chunsheng Zhu; Yanhong Li; Junjie Zhou; Yan Xu (PLoS ONE, 2025)
To enhance the mechanical and durability properties of cement-fly ash stabilized aeolian sand and crushed stones, the synergistic optimization effects of basalt fibers and polycarboxylate superplasticizer were investigated. First, two full factorial experiments were conducted to evaluate the individual and combined effects of basalt fiber volume content and polycarboxylate superplasticizer mass content. Then, four mix proportions were selected to verify the durability optimization. Finally, SEM, EDS, and XRD were used to elucidate the underlying micro-mechanisms. The results indicate that the optimal combination was 0.1% volume content of 12-mm-long basalt fibers and 1.0% mass content of polycarboxylate superplasticizer, which yielded a compressive strength of 13.3 MPa and a splitting tensile strength of 1.14 MPa at 28 days. Compared to the control group and individual addition of basalt fibers or polycarboxylate superplasticizer, the group with both basalt fibers and polycarboxylate superplasticizer had 33.00%, 16.67%, and 14.66% higher compressive strength and 52.00%, 31.03%, and 28.09% higher splitting tensile strength, respectively. Furthermore, the combined optimization improved the durability, decreased the thermal shrinkage by 49.85%, 32.35%, and 28.84%, and decreased the drying shrinkage by 68.95%, 33.15%, and 47.58%. The micro-experiments demonstrate that the bridging effect of basalt fibers during micro-crack formation and the synergistic action of polycarboxylate superplasticizer enhanced the uniformity and density of the mixture and that they are the primary factors that contribute to the strength development. Therefore, cement-fly ash stabilized aeolian sand and crushed stones can be optimized by using basalt fibers and polycarboxylate superplasticizer.